An Approximate Method of Measuring Excessive Production or Consumption - Selden, G. C. (Quarterly Journal of Economics, 1900)
An Approximate Method of Measuring Excessive Production or Consumption Get access G. C. Selden G. C. Selden Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 15, Issue 1, November 1900, Pages 138–142, https://doi.org/10.2307/1885864 Published: 01 November 1900